Indigenous rhizobium and its effect on the success of inoculation - Suryantini Suryantini (Balai Penelitian Tanaman Aneka Kacang dan Umbi, 2012)
Symbiotic nitrogen fixationis a key factor in the low-input farming systemto sustain long time soil fertility. Symbiotic nitrogenfixation involving host-specific symbiotic interactionsbetween root nodule bacteria, termed rhizobia,and legumes. One of the major strategies forenhancing symbiotic nitrogen fixation by legumesin crop production systems is through rhizobialinoculation. But inoculation not always successfuland one reason is the population of indigenous rhizobiumcontained in the soil. Indigenous rhizobium cancompete with rhizobium inoculant through populationdensity and effectiveness. The high populationof rhizobium in one place relating to the type oflegume that ever grew / grown. When the numberof indigenous population is low, not effective or notcompatible with legumes planted the rhizobiuminoculation is required. But when the number ofindigenous rhizobium population is high, effectiveand compatible with legumes that will be planted(based on observations of root nodules and existingplants), inoculation is not required.